A Comprehensive Study of Formic Acid Oxidation on Palladium Nanocrystals with Different Types of Facets and Twin Defects. Issue 14 (13th April 2015) - Choi, Sang‐Il; Herron, Jeffrey A.; Scaranto, Jessica; Huang, Hongwen; Wang, Yi; Xia, Xiaohu; Lv, Tian; Park, Jinho; Peng, Hsin‐Chieh; Mavrikakis, Manos; Xia, Younan
Abstract Palladium has been recognized as the best anodic, monometallic electrocatalyst for the formic acid oxidation (FAO) reaction in a direct formic acid fuel cell. Here we report a systematic study of FAO on a variety of Pd nanocrystals, including cubes, right bipyramids, octahedra, tetrahedra, decahedra, and icosahedra. These nanocrystals were synthesized with approximately the same size, but different types of facets and twin defects on their surfaces. Our measurements indicate that the Pd nanocrystals enclosed by {1 0 0} facets have higher specific activities than those enclosed by {1 1 1} facets, in agreement with prior observations for Pd single‐crystal substrates. If comparing nanocrystals predominantly enclosed by a specific type of facet, {1 0 0} or {1 1 1}, those with twin defects displayed greatly enhanced FAO activities compared to their single‐crystal counterparts. To rationalize these experimental results, we performed periodic, self‐consistent DFT calculations on model single‐crystal substrates of Pd, representing the active sites present in the nanocrystals used in the experiments. The calculation results suggest that the enhancement of FAO activity on defect regions, represented by Pd(2 1 1) sites, compared to the activity of both Pd(1 0 0) and Pd(1 1 1) surfaces, could be attributed to an increased flux through the HCOO‐mediated pathway rather than the COOH‐mediated pathway on Pd(2 1 1). Since COOH has been identified as a precursor to CO, a site‐poisoning species, a lower coverage of CO at the defect regions will lead to a higher activity for the corresponding nanocrystal catalysts, containing those defect regions.